The effectiveness of physical literacy interventions: a systematic review with meta-analysis - Carl, Johannes; Barratt, Jaime; Wanner, Philipp; Töpfer, Clemens; Cairney, John; Pfeifer, Klaus (Sports medicine, 2022)
The holistic concept of physical literacy assumes that individuals require adequate cognitive (knowledge and understanding), affective (motivation and confidence), and physical (physical competence) qualities to engage in lifelong physical activity behavior. In recent years, the research field has undergone rapid development and has also yielded an increasing number of interventions that aim to translate the theoretical-philosophical ideas into practical endeavors.